2018
DOI: 10.21511/bbs.13(3).2018.03
|View full text |Cite
|
Sign up to set email alerts
|

IFRS compliance and stock prices influence: evidence from Jordanian banks

Abstract: This study aims to examine the IFRS compliance in Jordanian banks and its relation to stock prices. The impact of compliance with International Financial Reporting Standards (IFRS) on stock prices in Jordanian banks is a rarely researched subject in accounting and finance, but whether IFRS compliance has a serious impact on stock prices, particularly in developing countries, is still unknown. Numerous factors in developing countries, such as cultural, political, and economic circumstances, can create different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Figure 3 shows development in total and tax revenues for two non-resource groups (non-resource Maghreb and Mashreq) and three resource groups (resource Maghreb, GCC and OME). The levels and trajectories of total revenues for non-resource Maghreb and Mashreq have been broadly similar, but have diverged in recent years; in the Mashreq, revenues declined sharply across all constituent countries (Egypt, Jordan, Lebanon and presumably, Syria), by an average of about five percentage points of GDP (Harrigan, 2014; Mansour, 2015; Almasarwah et al , 2018). More significant, however, are the differences in tax revenues between these two groups: Maghreb countries tended to raise more than Mashreq countries – about 6.4 per cent points of GDP on average; and, moreover, Mashreq tax revenues were stagnant while those in the Maghreb increased between 2005 and 2012.…”
Section: The Discussion and Resultsmentioning
confidence: 99%
“…Figure 3 shows development in total and tax revenues for two non-resource groups (non-resource Maghreb and Mashreq) and three resource groups (resource Maghreb, GCC and OME). The levels and trajectories of total revenues for non-resource Maghreb and Mashreq have been broadly similar, but have diverged in recent years; in the Mashreq, revenues declined sharply across all constituent countries (Egypt, Jordan, Lebanon and presumably, Syria), by an average of about five percentage points of GDP (Harrigan, 2014; Mansour, 2015; Almasarwah et al , 2018). More significant, however, are the differences in tax revenues between these two groups: Maghreb countries tended to raise more than Mashreq countries – about 6.4 per cent points of GDP on average; and, moreover, Mashreq tax revenues were stagnant while those in the Maghreb increased between 2005 and 2012.…”
Section: The Discussion and Resultsmentioning
confidence: 99%
“…Contrariwise, El-Diftar and Elkalla (2019) compare firms operating in the Gulf Cooperation Council (GCC) with non-GCC countries from the MENA region and conclude that IFRS adoption harms value relevance. In addition to traditional determinants, such as firms' reporting incentives, including ownership dynamics around IFRS adoption (Hessayri and Saihi, 2018), or the enforcement regime's functionality, Almasarwah et al (2018) offer an alternative explanation of divergent results, one associated with frequent regional political and economic turmoil.…”
Section: Value Relevance Of Ifrs In Saudi Arabiamentioning
confidence: 99%
“…With regard to the effect of the degree of compliance, a number of studies have been conducted to identify the effect of the degree of compliance with IFRS on certain variables, IJAIM 29,4 for example, the correlation between the level of compliance with the IFRS and the share prices of Jordanian banks (Almasarwah et al, 2018), the impact of the level of compliance with IFRS 7 on the performance of European banks (Carlo and Steck, 2011), the impact of risk disclosure on banks' credit ratings within the availability of governance structures as a mediator (Elamer et al, 2021) and risk disclosure practices in light of religious governance (quality of Islamic governance and quality of national governance) (Elamer et al, 2020a(Elamer et al, , 2020b. On the other hand, some studies have attempted to identify the factors affecting risk disclosure and found that one of the most important factors is corporate governance (Al-Hadi et al, 2016;Al-Hadi et al, 2019;Elamer et al, 2020aElamer et al, , 2020b.…”
Section: Literature Review 21 International Financial Reporting Standard and Cost Of Equity Capitalmentioning
confidence: 99%